2018
DOI: 10.4269/ajtmh.18-0214
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry and Malaria among Children in Niger: A Cross-Sectional Study

Abstract: The complex relationship between malnutrition and malaria affects morbidity and mortality in children younger than 5 years, particularly in parts of sub-Saharan Africa where these conditions occur together seasonally. Previous research on this relationship has been inconclusive. Here, we examine the association between anthropometric indicators and malaria infection in a population-based sample of children younger than 5 years in Niger. This cross-sectional study is a secondary analysis of a cluster-randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…e age of the children, as well as anthropometric parameters such as WHZ, HAZ, BAZ, and MUACZ, had no significant impact on the occurrence of the disease. is result corroborates those of O'brien et al (2018) who also found no association between several anthropometric parameters (HAZ, WAZ, WHZ, and MUACZ) and malaria infection [15]. However, we noted that children with acute malnutrition (WAZ) seem to develop less the disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…e age of the children, as well as anthropometric parameters such as WHZ, HAZ, BAZ, and MUACZ, had no significant impact on the occurrence of the disease. is result corroborates those of O'brien et al (2018) who also found no association between several anthropometric parameters (HAZ, WAZ, WHZ, and MUACZ) and malaria infection [15]. However, we noted that children with acute malnutrition (WAZ) seem to develop less the disease.…”
Section: Discussionsupporting
confidence: 93%
“…However, the exact mechanism of this protective effect remains difficult to explain. According to O'brien et al (2018), the potential mechanism of this relationship is twofold, namely, behavioural through the protection of some malnourished people by mothers and caregivers and biological through the immunomodulatory effect of nutritional status or the increase in the ability of malnourished children to produce certain cytokines in response to stimulation by malaria-specific antigens [15]. In this study, malnourished refugee children supplemented with multivitamins may their effect affects positively the immune system of these children.…”
Section: Discussionmentioning
confidence: 69%
“… 4 A previous study in Niger conducted at the beginning of the malaria season found evidence of a small increase in malaria parasitemia with fever in children with higher height-for-age Z -scores (HAZ), but no other evidence of an association between nutritional status and malaria. 5 A systematic review of studies of the relationship between malaria and malnutrition concluded that the relationship is complex and called for analysis of additional individual patient data of malaria and malnutrition in different settings. 4 Poor nutritional status may predispose children to infection with malaria by modulating immune function, and children with malaria may be predisposed to malnutrition, particularly if they suffer from repeated infection.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition and malaria are among the leading causes of morbidity and mortality among children in developing countries [1,2]. Though the relationship between the two conditions still remains controversial, there are scores of extant literature attesting to the existence of epidemiological association between malnutrition and infectious diseases generally [3][4][5][6]. The nature of such association has usually been considered to be a synergistic one -malnutrition could increase susceptibility to infection such as malaria, while episodes of infection or malaria can also precipitate nutritional deficiencies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%